Exposure–Response Analysis of Cardiovascular Outcome Trials With Incretin-Based Therapies - Pan, Qi; Yuan, Mingxia; Guo, Lixin (Frontiers in Endocrinology, 2022)
Our study aimed to evaluate the exposure–response relationship between incretin-based medications and the risk of major adverse cardiovascular events (MACE) using cardiovascular outcome trials (CVOTs). Eleven CVOTs with incretin-based medications were included. The median follow-up time, percentage of time exposure, and hazard ratio (HR) of MACE were obtained from each CVOT. The pharmacokinetic parameters of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and dipeptidyl peptidase-4 inhibitor (DPP-4) were obtained from published studies. Regression analysis was performed to assess the relationship between drug exposure and MACE HR. Cutoff values were determined from the ROC curves. The linear regression results indicated that log Cmax, log AUC0–24h, and log AUCCVOT are negatively correlated with MACE HR (R2 = 0.8494, R2 = 0.8728, and R2 = 0.8372, respectively; all p < 0.0001). The relationship between drug exposure (log Cmax, log AUC0–24h, and log AUCCVOT) and MACE HR strongly corresponded with the log (inhibitor) vs. response curve (R2 = 0.8383, R2 = 0.8430, and R2 = 0.8229, respectively). The cutoff values in the ROC curves for log Cmax, log AUC0–24h, and log AUCCVOT, were 2.556, 3.868, and 6.947, respectively (all p = 0.007). A Fisher’s exact test revealed that these cutoff values were significantly related to cardiovascular benefits (all p < 0.05). Our study revealed a linear exposure–response relationship between drug exposure and MACE HR. We conclude that the cardiovascular benefits of incretin-based therapies may occur with higher doses of GLP-1 RAs and with increased exposure.